Patients' experience of trauma care in the emergency department of a major trauma centre in the UK. (November 2017) - Skene, Imogen; Pott, Jason; McKeown, Eamonn
Highlights: The concept of liminality helps to frame the trauma patients journey through the ED. Compassionate and competent care promotes feelings of safely in trauma patients'. Communication promotes trust in the trauma team. A clean environment promotes professionalism and safely to the trauma patients'.